Cancer immunotherapy using PolyPurine Reverse Hoogsteen hairpins targeting the PD-1/PD-L1 pathway in human tumor cells - Medina Enríquez, Miriam Marlene (PLoS One, 2018)
Immunotherapy approaches stand out as innovative strategies to eradicate tumor cells. Among them, PD-1/PD-L1 immunotherapy is considered one of the most successful advances in the history of cancer immunotherapy. We used our technology of Polypurine reverse Hoogsteen hairpins (PPRHs) for silencing both genes with the aim to provoke the elimination of tumor cells by macrophages in co-culture experiments. Incubation of PPRHs against PD-1 and PD-L1 decreased the levels of mRNA and protein in THP-1 monocytes and PC3 prostate cancer cells, respectively. Viability of THP-1 cells and macrophages obtained by PMA-differentiation of THP-1 cells was not affected upon incubation with the different PPRHs. On the other hand, PC3 cell survival was partially decreased by PPRHs against PD-L1. The greatest effect in decreasing cell viability was obtained in macrophages/PC3 co-culture experiments by combining PPRHs against PD-1 and PD-L1. This effect was also observed in other cancer cell lines: HeLa, SKBR3 and to a minor extent in M21. Apoptosis was not detected when macrophages were treated with the different PPRHs. However, co-cultures of macrophages with the four cancer cell lines treated with PPRHs showed an increase in apoptosis. The order of fold-increase in apoptosis was HeLa > PC3 > SKBR3 > M21. This study demonstrates that PPRHs could be powerful pharmacological agents to use in immunotherapy approaches for the inhibition of PD-1 and PD-L1.